MODERN METHODS OF EARLY DETECTION OF PREDICTORS OF DEVELOPMENT OF CARDIOVASCULAR DISEASES IN CHILDREN - Arzibekov Abdikadir Gulyamovich (Galaxy International Interdisciplinary Research Journal, 2025)
Cardiovascular diseases are the main cause of disability and premature death in economically developed countries. The share of cardiovascular diseases in the mortality structure reaches 40-60%. The incidence of cardiovascular diseases among children and adolescents increases annually. Increased variability of blood pressure in patients with arterial hypertension at a young age is a factor that aggravates the violation of arterial rigidity. The aim of the study is to develop early diagnostic methods for cardiovascular diseases in children to reduce the incidence of primary and recurrent complications in the future.